New attack based on smartwatch motion sensors and the protection method research - Chen-guang SONG; Jian-wei LIU; Qian-hong WU; Zhen-yu GUAN (Tongxin xuebao)
Smart watch shipped with various embedded motion sensors,such as the accelerometer and gyroscope.Smart watch can follow the movement of hand to recognize the corresponding displacement,so that others can steal user’s external keyboard input through smart watches.The feasibility of intelligent device based on 6 axis accelerometer/gyroscope to infer the user’s keyboard input was researched,and the user’s keyboard input kinematic model for motion classification recognition was established.When users perform sensitive inputting,such as passwords inputting on digital keyboard,the passwords according to sensor information can be deduced.The results show that the approach can effectively recognize the PIN code on keyboard,which absolutely prove the seriousness of this safety problem.